Quantitative analysis of geometric information from an end‐to‐end examination of IMRT and VMAT using the optimal selection method. Issue 6 (22nd May 2013) - Tachibana, Hidenobu; Takahashi, Ryo
Abstract : Purpose: Gamma index, distance‐to‐agreement, and dose difference (DD) are commonly used to evaluate planar dose distributions. In this evaluation, the agreement between calculated and measured dose distributions can be susceptible to steep dose gradients along another axis perpendicular to the evaluation plane. Visual registration of the measured dose distribution may be performed to achieve better agreement, although doing so might lose geometric information related to beam targeting in an end‐to‐end test of intensity modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT). The optimal selection (OS) method was developed to take into consideration a dose distribution in three‐dimensions, and also to quantitatively analyze geometric information along with better agreement. Methods: The OS method was composed of two steps. These steps were based on two algorithms, the gamma index and DD, to (1) find the best‐matched plane, which is parallel to the planar measured dose distribution and is reconstructed by a volumetric dose distribution calculated by a treatment planning system; and (2) to get shifts and rotation along with better agreement between the calculated and measured dose distribution, compared with the planar dose distribution from the test. The OS method computes shifts and rotation against a user‐defined coregistered location for the measured dose distribution. Thirteen prostate IMRT plans (two planes per plan for a total of 26 planes) were analyzed retrospectively to compare the pass ratios of DD and gamma index evaluations with and without the OS method. The computed shifts and rotations were evaluated. Results: Compared with the method without OS, the average pass ratios of DD and gamma index with the OS method increased by 8.2% and 5.7%, respectively, in the dose region from 30% to 100%. A particular result from one of the planes showed an increase of 43.5% and 32.5% in the pass ratios of DD and gamma, respectively, with the OS method in the same dose region. The shifts in the x‐, y‐, z‐axes and rotation, which were computed using the OS method, were 0.5 ± 0.6, 0.3 ± 0.5, 1.0 ± 1.1 mm, and 0.3 ± 0.3°, respectively. In terms of the comparatively large difference between the z‐shift and the x‐ and y‐shifts, an additional geometric test was performed. A systematic error of 0.7 mm in the z‐axis was found at the location of the film placed in the phantom that we used. Conclusions: The OS method improved the quality of the end‐to‐end test of IMRT and VMAT plans by providing additional information regarding shifts and rotation, which were calculated and found to be in better agreement.